The Emerging Role of Exosomes in the Treatment of Human Disorders With a Special Focus on Mesenchymal Stem Cells-Derived Exosomes - Ghafouri-Fard, Soudeh; Niazi, Vahid; Hussen, Bashdar Mahmud; Omrani, Mir Davood; Taheri, Mohammad; Basiri, Abbas (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are produces by diverse eukaryotic and prokaryotic cells. They have prominent roles in the modulation of cell-cell communication, inflammation versus immunomodulation, carcinogenic processes, cell proliferation and differentiation, and tissue regeneration. These acellular vesicles are more promising than cellular methods because of the lower risk of tumor formation, autoimmune responses and toxic effects compared with cell therapy. Moreover, the small size and lower complexity of these vesicles compared with cells have made their production and storage easier than cellular methods. Exosomes originated from mesenchymal stem cells has also been introduced as therapeutic option for a number of human diseases. The current review aims at summarization of the role of EVs in the regenerative medicine with a focus on their therapeutic impacts in liver fibrosis, lung disorders, osteoarthritis, colitis, myocardial injury, spinal cord injury and retinal injury.